Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy revisited: Genotype-phenotype correlations of all published cases. (June 2020) - Xiromerisiou, Georgia; Marogianni, Chrysoula; Dadouli, Katerina; Zompola, Christina; Georgouli, Despoina; Provatas, Antonios; Theodorou, Aikaterini; Zervas, Paschalis; Nikolaidou, Christina; Stergiou, Stergios; Ntellas, Panagiotis; Sokratous, Maria; et al.
Abstract : Objective: The aim of this study was to evaluate the correlation between the various NOTCH3 mutations and their clinical and genetic profile, along with the presentation of a novel mutation in a patient. Methods: Here, we describe the phenotype of a patient with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) harboring a novel mutation. We also performed an extensive literature research for NOTCH3 mutations published since the identification of the gene and performed a systematic review of all published cases with NOTCH3 mutations. We evaluated the mutation pathogenicity in a great number of patients with detailed clinical and genetic evaluation and investigated the possible phenotype-genotype correlations. Results: Our patient harbored a novel mutation in the NOTCH3 gene, the c.3084 G > C, corresponding to the aminoacidic substitution p.Trp1028Cys, presenting with seizures as the first neurologic manifestation. We managed to find a correlation between the pathogenicity of mutations, severity of the phenotype, and age at onset of CADASIL. Significant differences were also identified between men and women regarding the phenotype severity. Conclusions: The collection and analysis of these scarce data published since the identification of NOTCH3 qualitatively by means of a systematic review and quantitatively regarding genetic profile and pathogenicity scores, highlight the significance of the ongoing trend of investigating phenotypic genotypic correlations.